Les adverbes de domaine en –wise : des marqueurs du Netspeak ? - Claude Guimier (Revue LISA)
Viewpoint –wise adverbs (such as education-wise, television-wise, basketball-wise) are commonly used on the Internet, so much so that they have been described as markers of Internet style. It is admitted that their development started in the 1940s, that is years before the advent of the Internet. If they are now found in all geographical varieties of English, not only in speech but also in newspapers, scientific journals, etc., their syntactic, semantic and morphological flexibility accounts for their extensive use on the Internet. This article presents some of their roles in the syntactic make-up of the sentence and in the organisation of the text.